Zygosity Test of Twin Pairs Using 26 STR Loci: A Case Study in Indonesian Population - Zarasade, Lobredia; Perdanakusuma, David S.; Notopuro, Harianto; Saamia, Vira; Furqoni, Abdul Hadi (Research Developments in Medicine and Medical Science Vol. 5, 2023)
The present study aims to determine zygosity in 12 twins with Non-Syndromic Cleft Lip and Palate (NSCLP) discordant, concordant, and non-NSCLP. Understanding the interaction between genes and environment can be aided by twin research. It is crucial to first categorise twins as monozygotic (identical) or dizygotic (fraternal) before beginning any research that will result in reliable results. Fraternal twins typically share 50% of their genes, compared to identical twins, who (theoretically) share 100% of their genes. The total sample were 12 Indonesian twin pairs, consist of 8 twins Non-syndromic Cleft Lip and Palate (NSCLP) discordant, 2 twins NSCLP concordant and 2 twins non-cleft (normal). DNA extraction was using Promega Kit and quantified was using Nano drop. DNA amplification was using PCR with 26 loci, which was packaged in Powerplex Fusion 6C Kit. PCR products were sequenced using ABI3500 and the visualization can be seen using GenemapperTM ID-X 1.6 software. The results show each pair of the 11 twins have similar allele in 26 STR loci, which mean they are monozygotic twins. Only 1 twin has different allele in 10 STR loci, which mean they are dizygote. The usage of STR in zygosity test is so far the gold standard due to the high sensitivity and the wide range of loci detection. The sensitivity and similarity of the zygosity test on MZ twins using STR loci are very high. The analysis of more STR loci would improve the accuracy of this test.